Maria Sklodowska Curie L'ostinata abnegazione di un genio - Dei, Luigi (Lectio Magistralis, 2013)
In 1911, the Nobel Prize for Chemistry was awarded to Marie Curie, eight years after she had received the Nobel Prize for Physics. An extraordinary scientific adventure ended, and the deification of an iconic character and symbol of the amazing transformations of costume which would characterize the following decades began to take root. During the transfer of the Curies' remains to the Pantheon, Pierre Gilles de Gennes wanted to underline Marie's "beauty of self-denial". The Christmas Lecture pays tribute to the dual inheritance which she left us: the strength of scientific rationality against the obscurantism of beliefs and gender equality. The conference traces the most relevant aspects of Marie Curie's life, sharing her extraordinary scientific discoveries, but also underlining socio-cultural and customary aspects and highlighting the historical context of an era which was tumultuously changing.